Social welfare and religion in the Middle East a Lebanese perspective - Jawad, Rana (Policy Press, 2009)
For a region which usually occupies media headlines and academic enquiry with concerns over global security and the supply of petroleum oil, the Middle East would appear averse to any talk of progressive social policy. As religion continues to regain its centrality in both academic and policy circles around the world, this book presents a new framework which examines the complex social and political dynamics shaping social welfare in the Middle East.